L-Arginine, the substrate for NO synthesis: an alternative treatment for premature atherosclerosis? - Siasos, G; Tousoulis, D; Antoniades, C; Stefanadi, E; Stefanadis, C (2007)
L-Arginine is the substrate of endothelial nitric oxide synthase (eNOS) and the main precursor of nitric oxide (NO) in the vascular endothelium. L-Arginine improves endothelial function in patients with hypercholesterolemia, hypertension and smokers, while its role in diabetes remains unclear. Oral supplementation of L-arginine leads to a significant improvement of endothelium-dependent forearm vasodilation in hypercholesterolemic patients, while intravenous infusion of L-arginine improves endothelial function in healthy smokers. L-Arginine has anti-hypertensive properties, although its effects on endothelial function in hypertensive patients needs further evaluation. In conclusion, L-arginine administration may be useful in patients with premature atherosclerosis.